Watching over Hong Kong : private policing 1841-1941 - Hamilton, Sheilah E. (Royal Asiatic Society Hong Kong studies series., 2008)
In this pioneering study, Sheilah Hamilton shows that, from the earliest days of British rule, the colonial administration introduced harsh legislation to control Chinese watchmen who were employed to protect the fledgling colony's property in the absence of an effective public police force.